Inhibitory effects of siwak (Salvadora persica. L) extract on the growth of Enterococcus faecalis planktonics and biofilms by in vitro - Ika Rhisty Cendana Sari; Rini Devijanti Ridwan; Diah Savitri Ernawati (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Enterococcus faecalis (E. faecalis) is one of the most persistent gram positive bacteria in root canal, resulting in secondary infection after endodontic treatment. E. faecalis pathogenicity is caused by overgrowth of E. faecalis planktonics and biofilms. E. faecalis planktonics produce lipoteichoid acid (LTA) as a virulence factor that can defend their permeability cell. On the other hand, E. faecalis biofilms produce protease, such as Esp (enterococcal surface protein), GelE (gelatinase), and SprE (serin protease), that have quorum-sensing mechanism as an adhesion factor to form extracellular polysaccharide substance (EPS) and increase the growth of the biofilms themselves. Siwak (Salvadora persica L.) has active components, namely benzylisothio-cyanate, trimethylamine, and salvadorine that can inhibit the growth of E. faecalis planktonics and biofilms. Purpose: This study aimed to measure inhibitory effects of siwak extract on the growth of E. faecalis planktonics and biofilms. Method: This research was an antimicrobial research on the culture of E.faecalis incubated in a TSB medium. Siwak extract was diluted into different concentrations, namely 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and 100%. The extract then was placed into the E. faecalis’s colony and planted into Trypticase Soy Agar medium. After incubated for 24 hours at 37°C, the colony would be measured and compared with the control (+) and control (-). As an antibiofilm research, this research used biofilm microtitter assay method to form E. faecalis biofilms incubated in a well-plate medium containing TSB and 0.1 % glucose. Siwak extract then was diluted into the same range concentration as in first method, and placed into the colony of E. faecalis to form biofilms. The biofilms were measured and compared to the control (+) given siwak extract and the control (-) given 0.1% chlorhexidine. After the incubation, they were washed three times, and staining process was conducted using Chrystal violet. The optical density then was measured by ELISA Reader 595 nm. Result: Siwak extract could inhibit the growth of E. faecalis planktonics at the concentration of 35% as a minimum inhibitory concentration as well as the growth of E. faecalis biofilms at the concentration of 45% as a minimum biofilm inhibitory concentration. Conclusion: Siwak extract has an inhibitory effect, particularly at a concentration of 35% on the growth of E. faecalis planktonics and at the concentration of 45% on the growth of E. faecalis biofilms.